Onchocerca eberhardi n. sp. (Nematoda: Filarioidea) from sika deer in Japan; relationships between species parasitic in cervids and bovids in the Holarctic region - Uni S.; Bain O.; Agatsuma T.; Harada M.; Torii H.; Fukuda M.; Takaoka H. (Parasite, 2007)
Onchocerca eberhardi n. sp. from the sika deer, Cervus nippon, in Japan is described. Adult worms lived in the carpal ligament; infection reached high levels (up to 25 female and 16 male worms in a single carpal limb). Skin dwelling microfilariae were mainly found in the ears. Prevalence of infection was 81 % at the type locality, Mt. Sobo, in Kyushu. The new material was compared to the 31 species of Onchocerca presently known. Onchocerca eberhardi n. sp. females were characterized by a long slender anterior end and a thin esophagus ≤ 1 mm long with no or only a slight glandular region. The vulva was located near the level of the mid-esophagus and the cuticle had transverse external ridges and internal striae (two striae between adjoining ridges). The most similar species were O. stilesi (re-examined), O. lienalis, and to a lesser extent O. gutturosa, all from bovids (cattle). Two main lineages of Onchocerca are recognized in cervids with either primitive or with derived characteristics (as exemplified by the new species). The species in both lineages are not restricted to cervids but are also found in bovids in the Holarctic region, suggesting that the species diversified in the two host groups simultaneously, when these host groups lived in the same geographic area.